Assessing the Role of Foreign Direct Investment in Strengthening China’s Economic Resilience and Sustainable Growth - Jia, ZhiBin; Ghosh, Abhijit (Journal of Ecohumanism, 2024)
This study explores the impact of Foreign Direct Investment (FDI) on China’s economic growth, industrial upgrading, and innovation capacity from 2000 to 2023. Using dynamic panel data models and spatial econometric methods, the research reveals that FDI has a significant positive impact on China’s economic growth quality. However, this effect varies significantly by region. The study also finds that FDI has facilitated the transformation of China’s industrial structure toward high-end industries and has promoted local innovation through technology spillovers. Based on the findings, the paper proposes policy recommendations for optimizing FDI structure, enhancing local integration, and fostering a regional innovation ecosystem.